Heterogeneity of Cholangiocarcinoma Immune Biology - Francesca Vita; Irene Olaizola; Francesco Amato; Colin Rae; Sergi Marco; Jesus M. Banales; Chiara Braconi (Cells, 2023)
Cholangiocarcinomas (CCAs) are aggressive tumors arising along the biliary tract epithelium, whose incidence and mortality are increasing. CCAs are highly desmoplastic cancers characterized by a dense tumor microenvironment (TME), in which each single component plays a fundamental role in shaping CCA initiation, progression and resistance to therapies. The crosstalk between cancer cells and TME can affect the recruitment, infiltration and differentiation of immune cells. According to the stage of the disease and to intra- and inter-patient heterogeneity, TME may contribute to either protumoral or antitumoral activities. Therefore, a better understanding of the effect of each immune cell subtype may open the path to new personalized immune therapeutic strategies for the management of CCA. In this review, we describe the role of immune cells in CCA initiation and progression, and their crosstalk with both cancer-associated fibroblasts (CAFs) and the cancer-stem-cell-like (CSC) niche.